User-Centered CASE Tools for User-Centered Information Systems - Campos, Pedro (2005)
The goal of this research is to design and evaluate a new generation of CASE tools, capable of clearly supporting all the styles of work adopted by teams of developers and capable of promoting Usability concerns to Informa tion Systems building. Our research approach is based on (a) creating usable and effective models of the developers behavior, and (b) building innovative, unconstrained collaborative prototypes that allow co-authoring of models by all stakeholders involved (programmers, marketers and interaction designers).